ON THE TECHNOLOGY FOR THE DEVELOPMENT OF SCIENTIFIC AND CREATIVE ACTIVITY IN STUDENTS - Ashurova , Laylo (Innovative Development in Educational Activities, 2023)
The article describes the essence and purpose of developing scientific and creative activities of students and the main factors of developing scientific and creative activities based on person-oriented education. The main factors determining the nature of scientific and creative activity are divided into groups such as philosophical and socio-economic activity and psychological and pedagogical activity, and their measurement categories are developed.